2021
DOI: 10.1002/jcaf.22514
|View full text |Cite
|
Sign up to set email alerts
|

Business strategy and systematic risk: Evidence from China

Abstract: Guided by their business strategies, firms develop their competitive advantages and overcome systematic risks by allocating their limited resources. This study explores how advertising, labor, R&D, cost, and capital intensities are correlated with the systematic risks of 10 industries in the Chinese market. The results show that these correlations vary between industries. To easily adapt to market variations and reduce systematic risks, decision‐makers are advised to design their business strategies according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Rahman et al. (2021) connected labor‐intensity to OL, and Taussig (2017) found that firms’ expenditures on employees relate to higher expected stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Rahman et al. (2021) connected labor‐intensity to OL, and Taussig (2017) found that firms’ expenditures on employees relate to higher expected stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Donangelo (2021) found that labor expenses, which relate to OL, explain approximately 50% of the value premium. Rahman et al (2021) connected labor-intensity to OL, and Taussig (2017) found that firms' expenditures on employees relate to higher expected stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%